2009
DOI: 10.1186/1471-244x-9-71
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic deficits and parvalbumin-containing inhibitory neurons in the prefrontal cortex in schizophrenia

Abstract: BackgroundWe have previously reported that the expression of the messenger ribonucleic acid (mRNA) for the NR2A subunit of the N-methyl-D-aspartate (NMDA) class of glutamate receptor was decreased in a subset of inhibitory interneurons in the cerebral cortex in schizophrenia. In this study, we sought to determine whether a deficit in the expression of NR2A mRNA was present in the subset of interneurons that contain the calcium buffer parvalbumin (PV) and whether this deficit was associated with a reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 90 publications
6
81
0
2
Order By: Relevance
“…For example, the density of dendritic spines and branches on layer 3, but not layer 5 pyramidal cells appears to be reduced in subjects with schizophrenia (Garey et al 1998;Glantz and Lewis 2000;Kalus et al 2000). Consistent with these findings, the somal area of layer 3 pyramidal cells (Pierri et al 2001) and the number of glutamatergic axon terminals in this layer, as visualized by vGluT1 (vesicular glutamate transporter 1) immunohistochemistry, have also been shown to be decreased in schizophrenia subjects (Bitanihirwe et al 2009). Because layer 3 pyramidal neurons furnish corticocortical connections that link the PFC to other cortical regions and because such large-scale networks are critical for the integrity of cognitive and perceptive functioning, disturbances of information processing carried out by circuits subserved by these neurons may contribute to a wide range of symptoms and cognitive deficits of the illness.…”
Section: Synaptic Connectivities In the Pfc Are Deficient In Schizophsupporting
confidence: 63%
See 1 more Smart Citation
“…For example, the density of dendritic spines and branches on layer 3, but not layer 5 pyramidal cells appears to be reduced in subjects with schizophrenia (Garey et al 1998;Glantz and Lewis 2000;Kalus et al 2000). Consistent with these findings, the somal area of layer 3 pyramidal cells (Pierri et al 2001) and the number of glutamatergic axon terminals in this layer, as visualized by vGluT1 (vesicular glutamate transporter 1) immunohistochemistry, have also been shown to be decreased in schizophrenia subjects (Bitanihirwe et al 2009). Because layer 3 pyramidal neurons furnish corticocortical connections that link the PFC to other cortical regions and because such large-scale networks are critical for the integrity of cognitive and perceptive functioning, disturbances of information processing carried out by circuits subserved by these neurons may contribute to a wide range of symptoms and cognitive deficits of the illness.…”
Section: Synaptic Connectivities In the Pfc Are Deficient In Schizophsupporting
confidence: 63%
“…In primary neuronal cultures, Kinney and colleagues have shown that NR2A expression in PV neurons is 5-fold greater than that in pyramidal cells (Kinney et al 2006), although it is unclear if this holds true in humans (Bitanihirwe et al 2009). Furthermore, NR2A, but not NR2B selective antagonist downregulates GAD 67 and PV expression in PV neurons (Kinney et al 2006).…”
Section: Deficient Glutamatergic Inputs May Contribute To the Dysfuncmentioning
confidence: 99%
“…PV cells mediate γ-band activity (8,9), and reduced PV immunoreactivity in inhibitory neurons is observed in schizophrenia (51)(52)(53). PV cells of the hippocampus are sparsely distributed, occurring primarily in stratum pyramidal, where they comprise up to 70% of the GABAergic neurons and a smaller portion of the interneurons in the adjoining areas of stratum oriens and stratum radiatum ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This present study is the first to use RNA interference to target the expression of VGLUT1 in a specific brain region in vivo as a novel means of manipulating synaptic glutamate release. Hippocampal expression of VGLUT1 mRNA and protein is decreased in schizophrenia (Eastwood and Harrison, 2005;Sawada et al, 2005;Piyabhan and Reynolds, 2006) and, although striatal deficits have also been reported (Piyabhan and Reynolds, 2006;Nudmamud-Thanoi et al, 2007), cortical changes (which do occur in depression; Gilabert-Juan et al, 2012) are far less robust in schizophrenia (Corti et al, 2007;OniOrisan et al, 2008;Uezato et al, 2009;Eastwood and Harrison, 2010) and appear restricted to specific layers of the prefrontal cortex (Eastwood and Harrison, 2005;Bitanihirwe et al, 2009), whereas the amygdala remains unaffected . The principal finding of the current study is that administration of a VGLUT1-targeting lentiviral shRNA vector into the dorsal hippocampus of Targeting whole-brain VGLUT1 expression using conventional gene knockout strategies results in a 35-41% decrease in transporter levels in heterozygous animals (Tordera et al, 2007;Garcia-Garcia et al, 2009).…”
Section: Discussionmentioning
confidence: 99%